Trace Elements in the Meat and Internal Organs of the Mountain Hare (Lepus timidus L., 1758) in the North of the Krasnoyarsk Region - Pavel V. Kochkarev; Maria A. Koshurnikova; Alexey A. Sergeyev; Valery V. Shiryaev (Техника и технология пищевых производств)
Relevant data on trace elements and toxic metals in game meat make it possible to monitor chemical pollution, as well as to detect risks to human and animal health. The authors used atomic absorption spectrometry to study iron, copper, zinc, lead, and cadmium in the skeletal muscles, liver, and kidneys of mountain hares (Lepus timidus L.) (n = 107). The animals were caught during two seasons on reference sites and technogenic territories in the northern Krasnoyarsk Region. The samples obtained from the hares that lived on the reference sites had a much lower content of toxic metals. The tissues that belonged to the hares from the polluted habitats contained more lead and cadmium while the samples from the reference sites demonstrated traces of such biogenic elements as copper, zinc, and iron. The differences may be associated with the antagonism of biogenic elements and toxic metals in the body. The correlations between various metals probably meant that they came from one and the same pollution source. The levels of cadmium and lead in the samples from the technogenic areas were not hazardous to animal health. However, their meat and liver were unfit to eat. Therefore, hunting in the areas of technogenic pollution can pose a toxic hazard to indigenous hunters and their families.